(untitled) (Research, Society and Development, 2021)
The objective was to describe the scientific evidence about psychosocial feelings and problems among health professionals in coping with COVID-19. It is an integrative review, carried out on the basis of MEDLINE and LILACS, during the period of May and June 2020, using the descriptors in health sciences and Boolean operator: Covid-19 AND Mental Health AND Professional, obtaining the total of 43 documents, chosen 10 for review. We observed that the isolation measures and other strategies taken for the prevention and control of the disease have caused several types of problems in the mental health of the professionals who are on the front line of the pandemic, affecting the lives of these people. It is possible to conclude that the present theme is of great relevance because the negative feelings generated by the disease can lead to more serious mental problems and it is essential to seek psychological support for these professionals.